1999
DOI: 10.1063/1.370710
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent microwave field and plasma discharge simulations for a moderate pressure hydrogen discharge reactor

Abstract: A self-consistent two-dimensional model of the electromagnetic field and the plasma in a hydrogen discharge system has been developed and tested in comparison to experimental measurements. The reactor studied is a 25 cm diameter resonant cavity structure operating at 2.45 GHz with a silica belljar of 10 cm diameter and 17 cm height contained within the microwave cavity. The inside of the belljar where the discharge occurs contains a substrate holder of 5 cm diameter that is used to hold substrates for diamond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(104 citation statements)
references
References 19 publications
10
92
2
Order By: Relevance
“…For typical process pressures, p >100 Torr, Tgas becomes sufficient for thermal dissociation of H2 to be the main route to producing H atoms. 63,67,71,74 The primary ionization mechanism also depends on the process conditions. Direct EI ionization of H2 (1), the sets of reactions (2) and (3) H2 + e  H2 + + 2e (1)…”
Section: H2 Plasmasmentioning
confidence: 99%
“…For typical process pressures, p >100 Torr, Tgas becomes sufficient for thermal dissociation of H2 to be the main route to producing H atoms. 63,67,71,74 The primary ionization mechanism also depends on the process conditions. Direct EI ionization of H2 (1), the sets of reactions (2) and (3) H2 + e  H2 + + 2e (1)…”
Section: H2 Plasmasmentioning
confidence: 99%
“…It has been suggested that these high vibrational levels are populated mainly through radiative decay of higher singlet electronic states excited by energetic electrons. 32,36,41 Since the exact vibrational distribution resulting from these processes is unknown, the effective rate coefficient for reaction ͑I-18͒ is no more than a rough estimate. The rate coefficient of reaction ͑I-17͒ is taken to be proportional to the excitation rates of H 2 (C 1 ⌸ u ) and H 2 (B 1 ⌺ u ϩ ); 36,41 the proportionality constant, however, is only a conjecture.…”
Section: Input Datamentioning
confidence: 99%
“…In order to get a perspective on the effect of operating parameters on conversion of hydrogen gas to its plasma state and its impact on the reduction process, a mention about average microwave power density (MWPD) is warranted [27,28]. The average power density is regulated through careful monitoring of microwave power and pressure.…”
Section: Microwave Power Densitymentioning
confidence: 99%